(untitled) (Journal of Eye Movement Research, 2015)
Purpose: Measuring near point of convergence (NPC) has recently emerged as a concussion assessment tool. Differences in administration of the test can be seen within the literature, which may affect results and normative values. There has been little investigation examining if clinically accessible target types affects NPC and no examination of NPC in a healthy, active young adult population. Methods: NPC was measured in 39 subjects using 5 different targets two times each with an accommodative ruler. Results: NPC ranged from 1.5-10cm in this population with an overall mean of 5.9+-1.6 cm. There were significant differences between the middle sized font and the line (p = .024) and pen (p = .047), and also between the largest sized font and the line (p = .026). Conclusion: For physically active young adults, the measurement of NPC is affected by target type.